SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN PINJAMAN MENGGUNAKAN APLIKASI FUZZY SIMPLE ADDITIVE WEIGHTING - Lorenso Kanuru; Dony M Sihotang; Bertha S Djahi (Universitas Nusa Cendana, 2018)
The loan service process is one of many routines applied to improve the welfare of either members or the community in cooperative. This process requires a high accuracy in selecting the eligible loans. Bad credits, that oftenly occurred in many cooperative membership, mainly caused by the lack of accuracy of the cooperative itself in selecting eligible loans based on the specific criterias. Implements and development for loan decision support system using Fuzzy Simple Additive Weighting (F-SAW) method. This method is able to accommodate the deficiancy of SAW in terms of providing linguistic assessments. The system is tested by comparing the system decision to the cooperative decision. According to 7 test data with loan amount below Rp 10,000,000 and 5 test data with loan amount between Rp 15,000,000 – Rp 20,000,000, it appears that 9 of them provide the same decision as what the committee decided (75%), while 3 of them do not (25%).